2010
DOI: 10.1002/cctc.201000309
|View full text |Cite
|
Sign up to set email alerts
|

An Atomic‐Scale View of Palladium Alloys and their Ability to Dissociate Molecular Hydrogen

Abstract: Palladium and its alloys play a central role in a wide variety of industrially important applications such as hydrogen reactions, separations, storage devices, and fuel‐cell components. Alloy compositions are complex and often heterogeneous at the atomic‐scale and the exact mechanisms by which many of these processes operate have yet to be discovered. Herein, scanning tunneling microscopy (STM) has been used to investigate the atomic‐scale structure of Pd–Au and Pd–Cu bimetallics created by depositing Pd on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 89 publications
8
102
1
Order By: Relevance
“…As established by the kinetic model, direct formation of hydrogen peroxide from hydrogen and oxygen seems to involve hydrogen adsorption, dissociation, but not spill-over of H-species over the AuPd surface. It is most likely that reaction occurs between non-dissociated oxygen and hydrogen species adsorbed pairwise as suggested by several studies on hydrogen adsorption over AuPd surfaces [53,54] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As established by the kinetic model, direct formation of hydrogen peroxide from hydrogen and oxygen seems to involve hydrogen adsorption, dissociation, but not spill-over of H-species over the AuPd surface. It is most likely that reaction occurs between non-dissociated oxygen and hydrogen species adsorbed pairwise as suggested by several studies on hydrogen adsorption over AuPd surfaces [53,54] .…”
Section: Discussionmentioning
confidence: 94%
“…Pd surface H 2 spill-over is impossible [53] . The formation of Pd ensembles is crucial for dissociative adsorption of hydrogen, considering that H ad is the most stable on Pd 3 threefold hollow sites, less stable on Pd 2 bridge sites and least stable on Pd monomers [54] .…”
Section: Kinetics Of Direct Formation Reactionmentioning
confidence: 99%
“…12,19,20 1. Dissociative and molecular chemisorption onto the catalyst surface A. Hydrogen dissociative chemisorption [21][22][23][24][25] At the equilibrium,…”
Section: 17mentioning
confidence: 99%
“…In several cases it has been shown that by doping the coinage metals with PGMs at very low molar fractions, such that these more reactive metals disperse as isolated single atoms in the surface layer of the host material, the activity of the coinage metal surface can be dramatically enhanced whilst retaining excellent reaction selectivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%